Disease modeling of a mutation in α‐actinin 2 guides clinical therapy in hypertrophic cardiomyopathy. Issue 12 (3rd November 2019) - Prondzynski, Maksymilian; Lemoine, Marc D; Zech, Antonia TL; Horváth, András; Di Mauro, Vittoria; Koivumäki, Jussi T; Kresin, Nico; Busch, Josefine; Krause, Tobias; Krämer, Elisabeth; Schlossarek, Saskia; Spohn, Michael; et al.
Abstract: Hypertrophic cardiomyopathy (HCM) is a cardiac genetic disease accompanied by structural and contractile alterations. We identified a rare c.740C>T (p.T247M) mutation in ACTN2, encoding α‐actinin 2 in a HCM patient, who presented with left ventricular hypertrophy, outflow tract obstruction, and atrial fibrillation. We generated patient‐derived human‐induced pluripotent stem cells (hiPSCs) and show that hiPSC‐derived cardiomyocytes and engineered heart tissues recapitulated several hallmarks of HCM, such as hypertrophy, myofibrillar disarray, hypercontractility, impaired relaxation, and higher myofilament Ca 2+ sensitivity, and also prolonged action potential duration and enhanced L‐type Ca 2+ current. The L‐type Ca 2+ channel blocker diltiazem reduced force amplitude, relaxation, and action potential duration to a greater extent in HCM than in isogenic control. We translated our findings to patient care and showed that diltiazem application ameliorated the prolonged QTc interval in HCM‐affected son and sister of the index patient. These data provide evidence for this ACTN2 mutation to be disease‐causing in cardiomyocytes, guiding clinical therapy in this HCM family. This study may serve as a proof‐of‐principle for the use of hiPSC for personalized treatment of cardiomyopathies. Synopsis: Disease modeling of a rare ACTN2 mutation in iPSC‐derived cardiomyocytes & heart tissues engineering revealed typical features of hypertrophic cardiomyopathy & electrophysiological anomalies. Diltiazem reversed the in vitro phenotypes & guided clinical therapy in the family, reducing QTc intervals. Modeling hypertrophic cardiomyopathy (HCM) with patient‐ and isogenic control‐derived hiPSC‐cardiomyocytes revealed higher cell area, myofibrillar disarray and higher LTCC density in 2D, and hypercontractility, prolonged relaxation and action potentials in 3D. Prolonged action potentials in 3D associated with higher LTCC currents in 2D, matching prolonged QT intervals and monophasic action potentials in HCM‐affected family members. Diltiazem normalized the electro‐mechanical phenotype in vitro and guided clinical therapy in the HCM affected family, reducing QTc intervals. This study may serve as proof‐of‐principle for the use of hiPSC‐cardiomyocytes and CRISPR/Cas9 for personalized treatment of cardiomyopathies. Abstract : Disease modeling of a rare ACTN2 mutation in iPSC‐derived cardiomyocytes & heart tissues engineering revealed typical features of hypertrophic cardiomyopathy & electrophysiological anomalies. Diltiazem reversed the in vitro phenotypes & guided clinical therapy in the family, reducing QTc intervals.